"Gente, por favor, fala um de cada vez.": etnografia, análise conversacional e inter-relações entre linguagem, cognição e cultura na comunidade dos Tipis - Eudenio Bezerra da Silva (2007)
Language, cognition and culture are taken as relational phenomena decurrent from the interlacing of our phylogenetic and ontogenetic histories in a given environment. Language is observed as an operational congruence, a conveyance in the environment. The basic,cognitive act is observed as the distinction /configuration of consensual objects and domain, in behavioral dynamics. Culture is observed as historical patterns of communicative actions correlated with cognition and language. Language is understood as occurring in a dynamic stability, as an action situated in cultural practices, in an emergent and contingent mode in which life is structured. The social-cultural practice of speech-in-interaction occurs as intelligibility situated for the practical aims which emerge in the activity itself, when an argumentative, perspective and engaged dimension is assumed, a world is retaken,reorganized and socially configurated. An ethnography of the Tipis backcountry community is presented as a collective production of the order. The practices and social cultural relations and the infra-structure conditions of the community consist of local linguisticinteractiveactivities and their interactions with other communities. The contexts of these practices are not previous to the tasks neither are they autonomous to their implementation: they shape themselves in the interaction, while molding it reflexively. It is proposed a conversational analyses of the procedures observed in a meeting of the Associação dosMoradores dos Tipis, where discursive topics are arisen by the participants, showing their listening, attention, comprehension, evaluation and intelligibility concerning what is being done.